2016
DOI: 10.1111/gcbb.12371
|View full text |Cite
|
Sign up to set email alerts
|

Biochar alters the soil microbiome and soil function: results of next‐generation amplicon sequencing across Europe

Abstract: Wide-scale application of biochar to soil has been suggested as a mechanism to offset increases in CO 2 emissions through the long-term sequestration of a carbon rich and inert substance to the soil, but the implications of this for soil diversity and function remain to be determined. Biochar is capable of inducing changes in soil bacterial communities, but the exact impacts of its application are poorly understood. Using three European sites [UK SRC, short rotation coppice, French grassland (FR) and Italian S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
60
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(65 citation statements)
references
References 91 publications
(154 reference statements)
4
60
0
1
Order By: Relevance
“…Consistent with previous studies based on 16S rRNA gene amplicons, we showed that Proteobacteria and Bacteroidetes relative abundances significantly increased in biochar-amended samples and that the relative abundance of Acidobacteria decreased (22,24,35,44). Overall, all classes of Proteobacteria were more abundant in the biochar-amended samples, consistent with our previous study (22) in which we observed that biochar increased Proteobacteria abundance in the oxisol as early as 1 month and up to 1 year after the initial amendment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies based on 16S rRNA gene amplicons, we showed that Proteobacteria and Bacteroidetes relative abundances significantly increased in biochar-amended samples and that the relative abundance of Acidobacteria decreased (22,24,35,44). Overall, all classes of Proteobacteria were more abundant in the biochar-amended samples, consistent with our previous study (22) in which we observed that biochar increased Proteobacteria abundance in the oxisol as early as 1 month and up to 1 year after the initial amendment.…”
Section: Discussionsupporting
confidence: 92%
“…While previous studies have used a single phylogenetic marker to investigate the effects of biochar on the soil microbial community (18,24,32,33,35), to date, only one has utilized shotgun metagenomics to examine the effects of biochar on the microbial community (42). Our results from the biochar-amended soil metagenomes showed some similarities to those of this previous study of biochar metagenomes (42).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…In some studies, it is even more desirable to focus on bacteria alone to centralize the effort and expenses to optimally address the research question. For example, in the field of bioremediation, several reports focus on re-structuring bacterial communities to improve the efficiency of organic contaminant degradation (Bell et al, 2013a,b; Thijs et al, 2016), monitor bacterial community structure in response to pollution (Truyens et al, 2013; Bell et al, 2015), or in response to agricultural management (Jenkins et al, 2016), plant genetic modification (Beckers et al, 2016), and to study the connections between plant-associated bacteria and human/animal microflora (Berg et al, 2015; Mahnert et al, 2015). For all these studies, next to universal prokaryotic primers, adequate bacteria-specific primers that are carefully selected in terms of coverage, reproducibility, exclusion of the amplification of host-organelles, and comparability between studies is needed.…”
Section: Introductionmentioning
confidence: 99%